1987
DOI: 10.1016/0035-9203(87)90248-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunity after treatment of human schistosomiasis mansoni. III. Long-term effects of treatment and retreatment

Abstract: Group mean Schistosoma mansoni reinfection patterns are presented for 2 years after treatment with oxamniquine in 1981 of over 100 9- to 16-year-old Kenyan schoolchildren, and for one year after retreatment in 1983 with either oxamniquine or praziquantel when most (nearly 700) infected people in the whole community were treated. Quality control confirmed comparable Kato egg counts throughout the study. Continuing transmission after 1981 raised prevalence to nearly its original level within 6 months, but intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Parasite intensity estimates were made prior to treatment each year, so the change in the FOI (expressed as a ratio of the FOI at baseline) is calculated as an average of the rising value across the previous year. The reductions in the FOI seen after each round were assumed to be equal across ages, as studies have shown that the infection profile generally returns to the same pattern following reinfection [36].…”
Section: Methodsmentioning
confidence: 99%
“…Parasite intensity estimates were made prior to treatment each year, so the change in the FOI (expressed as a ratio of the FOI at baseline) is calculated as an average of the rising value across the previous year. The reductions in the FOI seen after each round were assumed to be equal across ages, as studies have shown that the infection profile generally returns to the same pattern following reinfection [36].…”
Section: Methodsmentioning
confidence: 99%
“…The most often quoted values are 1-4 for the basic reproductive number and 4 years for the worm lifespan [1] and these values are used here. However, Woolhouse, Hasibeder and Chandiwana (unpublished observations) calculated higher values (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) for the basic reproductive number by taking into account acquired immunity and heterogeneity in exposure and contamination. Also, recent analysis of the worm lifespan suggests a longer lifespan of approximately 8 years (Fulford and colleagues, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Note that these are purely descriptive functions and do not model processes of birth and death. The data used in this [15] and Sturrock and colleagues [16]. See text for other details of programmes.…”
Section: Estimation Of Model Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect extremely significant is that in the reinfection after the treatment generally the individuals present reduction of the number of eggs in the stool (Kloetzel 1963, Prata et al 1980, Sturrock et al 1987.…”
Section: The Basic Achievementsmentioning
confidence: 99%